Problem Terapeutik pada Empiema Terlokulasi karena Tuberkulosis : [Theurapetic Problem in Tuberculosis Loculated Empyema] - Isnin Anang Marhana; Amelia Tantri Anggraeni (Faculty of Medicine Universitas Airlangga, 2018)
Background: Pleural effusion is the most common complication of pulmonary tuberculosis (TB). Some coexist with secondary infection could worsen clinical presentation as empyema. The incidence of pleural effusion in the early stage of empyema due to TB infection is about 31%. Somehow, untreated empyema increased in-hospital mortality. Case: A woman with unregulated diabetes mellitus was referred with organized empyema. The etiology of empyema is based on a specific process of TB infection with the ADA value of empyema fluid was 128 mg/dl. We decided to perform decortication with the result loculated empyema and bronchopleural fistula 2 cm in the inferior lobe of the right lung. The patient did not recover well. Unfortunately, fluidopneumothorax was found on a chest CT scan with contrast. Thoracotomy was performed and another bronchopleural fistula was found which length was about 1 cm in superior lobe of the right lung. Discussion: The worsening condition of the patient was caused by the occurrence of postoperative bronchopleural fistula. It was visualized as pulmonary TB with perforation of cavity nessessity. On the other hand, the condition could be worsened by the hyperglycemic state in an immunocompromised individual. Summary: Loculated empyema is a condition caused by bronchopleural fistula, the presence of a connecting cavity between pleural and bronchus which occurred less than 48 hours. Local and systemic factors might explain the development of bronchopleural fistula. Well management of the loculated empyema by knowing the etiology could improve the life survival of the patient.